Using profile of psychotropic drugs by users of the Psychosocial Care Center (CAPS) during the COVID-19 pandemic (Research, Society and Development, 2022)
The general objective of this research was to analyze the profile of psychotropic medication use by users of the Psychosocial Care Center (CAPS) in a municipality in the interior of Bahia during the SARS-cov-2 pandemic. This study is characterized as a descriptive and quantitative research through the analysis of reports of psychotropic drugs dispensed by CAPS between the years 2019-2022. The results found showed changes in the list of psychotropic drugs available at REMUNE (Municipal List of Essential Medicines), and mainly, an increase in the dispensation and use of psychotropic drugs, emphasizing benzodiazepines, during the COVID-19 pandemic. Thus, it is worth mentioning that the collaboration of the municipal and state public system, as well as public policies aimed at improvements and adherence to pharmacological treatments are extremely important for improving the mental health of the population, which was substantially affected by the pandemic.